Perspectivas del anciano latinoamericano a las puertas de un nuevo siglo - Luna Torres Leonor (Universidad Nacional de Colombia, 1997)
The world will beth scen ery of an unknocun success when this century finishes. The growing I old of the actual population is a reality that for latinamerica starts its evidence, this situation is starting to demand programs population, that give attention to the ancient population, the same that today registrat a life expectation of seventy (70) years and more for contries like Cuba, Colombia and Costa Rica. Although nation like Haiti and Dominican Republic can't even reach an average of sixty (60) years. The article describe the antecedents of the creation of policies and programs, calls the attention the important necesity of creatings new culture of the ancianity in the participation of the men, the family, the state and society in an explicit way to convoke the nursing professionals to participate in this iniciative.   El mundo será escenario de un hecho inédito al finalizar el presente siglo, el envejecimiento de la población, realidad que para América latina empieza a ser manifiesta, por consiguiente demanda políticas y programas que atiendan a la creciente población anciana, que hoy registra expectativa de vida de 70 y más años como el caso de Colombia, Cuba y Costa Rica respectivamente. Sin embargo países como Haití y República Dominicana no alcanzan los 60 años como expectativa de vida. El artículo narra los antecedentes en la formulación de políticas y programas, llama la atención de la inaplazable necesidad de crear una nueva cultura de la ancianidad con el concurso del anciano, la familia, el estado y la sociedad; de manera explícita convoca al profesional de enfermería a participar en esta iniciativa.